REFLECTION OF NIETZHES PHILOSOPHICAL IDEAS IN AVANGARDIZM ART - Ya. S. Demydenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the research is to explore the display of philosophical ideas of Nietzsche on the avangardism art. Methodology. The philosophical provisions, aesthetic, cultural and artistic ideas were used to identify the theoretical and methodological fundamentals. Scientific novelty. The influence of Nietzsche on the avangardism art was analyzed. Nietzsche’s views were relevant and demanded in the artistic culture of XX century, but at the same time, the representatives of the cultural traditions of the XX century, which used his creative ideas of the German philosopher, often referred to them very selectively and not always contextually correct. Conclusions. It was proved that the creative legacy of Nietzsche can be the intellectual base for overcoming the crisis in contemporary art culture and initiate the ascent of man to the new spiritual and artistic heights.